2021
DOI: 10.3390/microorganisms9040782
|View full text |Cite
|
Sign up to set email alerts
|

Different Responses of Bacterial and Archaeal Communities in River Sediments to Water Diversion and Seasonal Changes

Abstract: In recent years, different responses of archaea and bacteria to environmental changes have attracted increasing scientific interest. In the mid-latitude region, Fen River receives water transferred from the Yellow River, electrical conductivity (EC), concentrations of Cl- and Na+ in water, total phosphorus (TP), and Olsen phosphorus (OP) in sediments were significantly affected by water transfer. Meanwhile, temperature and oxidation-reduction potential (ORP) of water showed significant seasonal variations. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…This corroborates the partial Mantel test which showed that, compared to bacteria, archaea with a more compact network structure was less affected by environmental heterogeneity. This microbial group‐dependent difference may be because the higher diversity and faster growth rates of bacteria respond more swiftly to environmental disturbance than archaea (Fierer & Jackson, 2006; Lv et al, 2021). Furthermore, we found that features of the microbial network varied among river reaches––that is, species connectivity of the archaeal network was lowest and that of bacterial network was highest in midstream.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates the partial Mantel test which showed that, compared to bacteria, archaea with a more compact network structure was less affected by environmental heterogeneity. This microbial group‐dependent difference may be because the higher diversity and faster growth rates of bacteria respond more swiftly to environmental disturbance than archaea (Fierer & Jackson, 2006; Lv et al, 2021). Furthermore, we found that features of the microbial network varied among river reaches––that is, species connectivity of the archaeal network was lowest and that of bacterial network was highest in midstream.…”
Section: Discussionmentioning
confidence: 99%
“…After literature review, we found that the aqueous environment, as among the necessary conditions for the survival of flora, is closely related to the changes in the composition of flora (Or et al, 2007;Dechesne et al, 2008;Young et al, 2008;Dechesne et al, 2010;Vos et al, 2013). On the other hand, both the aqueous environment and the flora composition vary seasonally (Lv et al, 2021). Therefore, the present study mainly attempts to understand the relationship between host's intestinal water metabolism and seasonal differences in intestinal flora.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, although the sedimentary samples have a proximal distribution, variations were present, particularly for archaeal and eukaryotic communities. In addition, while eukaryotes, even fungi [75], are more sensitive to chloride than prokaryotes, studies have shown that bacteria are more sensitive to chlorides [76] and to environmental variations [77] than archaea. Thus, a small proportion of the chloride entering the sediment would have a stronger effect on these domains than on the archaea.…”
Section: Salinity Threshold For Microbial Community Transitionmentioning
confidence: 99%